Black butler. XXXII - Toboso, Yana, 1984- (Black butler, 2023)
"Baldo and Lau have uncovered the blood collection scheme at the Athena Sanitorium for Former Service men in record time, but the situation is not as cut-and-dry as they had assumed. While chief nurse Ada wants nothing more than to wash her hands of the whole affair, her duty to give the best care possible to her fellow veterans keeps her shackled to the Aurora Society. After all, the atrocities of war and the guilt of survival are heavy burdens to bear--ones that Baldo himself knows all too well..."--Back cover.